2019
DOI: 10.1029/2019jf004999
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Analysis of the Detachment and Impact Phases of a Rockfall and Application for Estimating Rockfall Volume and Free‐Fall Height

Abstract: We analyzed 21 rockfalls that occurred in limestone cliffs of the Chartreuse Massif (French Alps). These rockfalls were detected both by Terrestrial Laser Scanning or photogrammetry and by a local seismological network. The combination of these methods allowed us to study relations between rockfall properties (location of detachment and impacts areas, volume, geometry, and propagation) and the induced seismic signal. We observed events with different propagation modes (sliding, mass flow, and free fall) that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 39 publications
(130 reference statements)
4
29
0
Order By: Relevance
“…6f), which may correlate to the seismic response from the hillslope. This leading phase could easily be detected in the slope-scale monitoring of rockfall (Roy et al, 2019). The total duration associated with the detachment to deposition of approximately 16 seconds is consistent with the signal duration identified from the spectrogram of station ELDB (50 to 66 seconds in the video shown in Fig.…”
Section: Physical Processsupporting
confidence: 80%
See 2 more Smart Citations
“…6f), which may correlate to the seismic response from the hillslope. This leading phase could easily be detected in the slope-scale monitoring of rockfall (Roy et al, 2019). The total duration associated with the detachment to deposition of approximately 16 seconds is consistent with the signal duration identified from the spectrogram of station ELDB (50 to 66 seconds in the video shown in Fig.…”
Section: Physical Processsupporting
confidence: 80%
“…Recently, a simple scaling between the source magnitude and volume has been well established, covering a wide range of source volumes from 10 0 to 10 6 m 3 . But, there is a scatter trend in the data distribution for volumes ranging from 10 2 to 10 5 m 3 (Roy et al, 2019), which is shown in this research.…”
Section: Introductionmentioning
confidence: 45%
See 1 more Smart Citation
“…Quantifying rockfalls volumes from seismic signals is the subject of many studies (Dietze et al 2017;Hibert et al 2017;Le Roy et al 2019). Volumes can be derived from the characteristics of the seismic signal (duration, energy, amplitude) and are a function of the distance to the source, the type of ground impacted, the drop height, etc.…”
Section: Detection and Characterization Of Rockfalls 170mentioning
confidence: 99%
“…To determine the rock volume effectively involved in the landslide of May 29th 2018, it was decided to adopt a quantitative approach that minimizes the effect of the user-related bias (interpretation and manual delimitation of the sliding and the external surfaces of the rockfall), similar to those applied in [35][36][37].…”
Section: Post-failure Analysismentioning
confidence: 99%